2022
DOI: 10.1002/kjm2.12503
|View full text |Cite|
|
Sign up to set email alerts
|

CERS6‐AS1 contributes to the malignant phenotypes of colorectal cancer cells by interacting with miR‐15b‐5p to regulate SPTBN2

Abstract: Accumulating evidence indicates that long noncoding RNAs (lncRNAs) act as tumor promoters or suppressors in various types of cancer. Previous investigations suggest that ceramide synthase 6 (CERS6) antisense RNA 1 (CERS6-AS1) acts as an oncogene in breast cancer; however, its role in colorectal cancer is unknown. This study aimed to explore the molecular mechanism of CERS6-AS1 in colorectal cancer. Gene expression in colorectal cancer was examined using reverse transcription-quantitative polymerase chain react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…CSCs in oral/oropharyngeal squamous cell carcinoma enhance the tumorigenicity and self-renewal abilities of cancer cells in vivo 56 , 57 . Moreover, many studies have reported that Linc00662 enhances cell stemness in breast cancer/osteosarcoma by sponging miR-144-3p/miR-16-5p 22 , 35 , and that lncRNA CERS6-AS1 acts as an oncogene that facilitates xenograft tumor growth by binding to miR-15b-5p 29 . Consistent with previous findings, we demonstrate that the Linc00662 / miR-15b-5p axis affects tumor cell growth stemness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CSCs in oral/oropharyngeal squamous cell carcinoma enhance the tumorigenicity and self-renewal abilities of cancer cells in vivo 56 , 57 . Moreover, many studies have reported that Linc00662 enhances cell stemness in breast cancer/osteosarcoma by sponging miR-144-3p/miR-16-5p 22 , 35 , and that lncRNA CERS6-AS1 acts as an oncogene that facilitates xenograft tumor growth by binding to miR-15b-5p 29 . Consistent with previous findings, we demonstrate that the Linc00662 / miR-15b-5p axis affects tumor cell growth stemness.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, lncRNAs act as sponges for miRNAs to influence the progression of cancer cell stemness [23][24][25][26][27]. There is increasing research on the roles of lncRNAs and miR-15b-5p in the occurrence and development of cancer [28][29][30]. However, the role and function of Linc00662 and miR-15b-5p in HSCC and their effects on tumor cell stemness have not been completely elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Wang et al ( 12 ) suggested that SPTBN2 inhibition is implicated in halting proliferation, migration and invasion of endometrioid endometrial cancer cells. SPTBN2 upregulation promotes the proliferation, migration and invasion of colorectal cancer cells ( 30 ). Consistent with these findings, the present study demonstrated that SPTBN2 knockdown suppressed the proliferation, migration and invasion of A2780 cells, suggesting the oncogenic role of SPTBN2 in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated that the upregulated lncRNA JPX promoted lung cancer proliferation and metastasis by the JPX/miR-33a-5p/Twist1 axis activating Wnt/β-catenin signaling both in vitro and in vivo [ 7 ]. Zhao et al reported that the lncRNA CERS6-AS1 facilitates proliferation, migration and invasion in colorectal cancer cells by affecting miR-15b-5p to upregulate SPTBN [ 8 ].…”
Section: Introductionmentioning
confidence: 99%